Patient Deception: Nursing Students' Beliefs and Attitudes. Issue 5 (September 2015) - Curtis, Drew A.
Abstract : This study examined nursing students' beliefs about indicators of deception and their attitudes toward patient deception. Fifty-eight participants from various nursing programs at a southwestern university completed a Detection of Deception Questionnaire and Attitudes Toward Patient Deception Scale. Findings indicated that nursing students have a number of inaccurate beliefs about deception and possess a number of negative attitudes toward patients who lie. Implications for nursing education are discussed.